Geopolymer concrete dry blend as well as preparation method and application thereof
The design of single-component geopolymer dry mix using ternary solid activators and steel fiber reinforcement mechanisms solves the problems of excessively rapid early setting and insufficient strength of UHPGC, achieving high strength, long setting time and high toughness, and simplifying the construction process.
Patent Information
- Application Number
- CN202511220346.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-11-18
AI Technical Summary
In the existing technology, the preparation of ultra-high performance geopolymer concrete (UHPGC) is complicated and has problems such as excessively rapid early setting, poor fluidity, and insufficient toughness, making it difficult to achieve both ultra-high strength and controllable setting.
A ternary solid activator system, including silicate-type, caustic alkali-type, and weak acid salt-type activators, is adopted in conjunction with a steel fiber reinforcement mechanism to form a single-component geopolymer concrete dry mix. The solid activators control the setting rate and promote the formation of a dense cementitious structure through synergistic effects, while the steel fibers enhance the toughness of the material.
It achieves long initial setting time, high strength and high toughness, simplifies the construction process, and improves the material's construction adaptability and feasibility in engineering applications.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building materials, in particular to a geopolymer concrete dry mixture and a preparation method and application thereof. BACKGROUND
[0002] As a green cementitious material, geopolymer cementitious material is prepared by using silicon-aluminum solid waste as raw material and generating gel structure through alkali activation. It has significant advantages in reducing energy consumption and CO2 emission. Geopolymer materials can be divided into single component and double component according to their mixing methods. The traditional double component geopolymer system is composed of liquid alkali activator and solid aluminosilicate precursor; while the single component geopolymer is prepared by mixing solid activator with powder in advance, and then activated by adding water during use, which significantly improves the construction convenience and safety, and is more close to the construction logic of cement-based materials. In addition, the alkali aluminosilicate gel structure generated by solid activator is more compact than the hydrated calcium silicate in cement system, and has faster early strength development, which effectively solves the performance trade-off problem between setting rate and mechanical properties of traditional geopolymer system.
[0003] Ultra-high performance concrete (UHPC) is a new type of building material with excellent mechanical properties and durability. It is designed based on the close packing theory of raw materials, and by adding ultra-fine auxiliary cementitious materials and increasing the amount of superplasticizer, low water-binder ratio and high system density are achieved. However, the amount of Portland cement used in the preparation of traditional UHPC is as high as 800-1100 kg / m 3 , which greatly increases the economic cost and environmental burden.
[0004] Ultra-high performance geopolymer concrete (UHPGC) prepared based on green geopolymer helps to achieve the dual effect of material performance indicators and green low-carbon requirements. However, there are few studies on UHPGC at present, and the basic theory and preparation technology of its composition design are still in the preliminary development stage. In the prior art, the preparation of UHPGC usually needs to add multiple components including mineral powder, fly ash, silica fume, activator, water reducing agent, etc. on site, which is complex to operate, and has technical bottlenecks such as fast early setting, poor fluidity and insufficient toughness, which seriously restricts its engineering promotion. Studies have shown that the type and combination of activators have a decisive effect on the setting behavior and mechanical properties of geopolymer materials. Traditional activators such as Na2O·2SiO2 can quickly promote polymerization, but they can easily cause rapid setting, affecting construction operation and structural integrity.
[0005] CN 202411454053.0 discloses a preparation method of solid waste cementing material based on phosphate-silicate composite excitation. The chemical bonding reaction of phosphate and calcium ions promotes the generation of hydration products, thereby enhancing the early strength. However, the inherent liquid phosphate coagulation of this mechanism leads to an initial setting time of less than 60 minutes, which is difficult to meet the construction requirements of complex components, and the calcium phosphate network structure is not dense enough, with a compressive strength of only 54 MPa, which does not effectively enhance the toughness performance. In addition, this formula relies on liquid modifiers, which limits its application in the preparation of single-component dry mix.
[0006] Therefore, it is urgent to develop a single-component ultra-high performance geopolymer concrete dry mix, which breaks through the technical bottleneck that ultra-high strength and controllable setting are difficult to achieve simultaneously in geopolymer materials for a long time. SUMMARY
[0007] The purpose of the present application is to overcome the above technical deficiencies, provide a geopolymer concrete dry mix and its preparation method and application, and solve the technical problem that ultra-high strength and controllable setting are difficult to achieve simultaneously in geopolymer materials for a long time in the prior art.
[0008] To achieve the above technical purpose, the technical scheme of the present application provides a geopolymer concrete dry mix, the raw materials are calculated according to the mass fraction, including 20-85 parts of mineral powder; 10-35 parts of fly ash; 5-30 parts of silica fume; 5-20 parts of solid alkali activator A; 2-10 parts of solid alkali activator B; 0.5-10 parts of solid alkali activator C; 0-10 parts of water reducing agent; 50-200 parts of quartz sand; the solid alkali activator A is a silicate type activator; the solid alkali activator B is a caustic alkali type activator; the solid alkali activator C is a weak acid strong base salt, and the solubility product of the selected salt is lower than that of hydrated calcium silicate, which can generate a low solubility precipitate with calcium ions in the system, thereby delaying the formation of hydrated calcium silicate and achieving the effect of retarding.
[0009] In any embodiment, the solid alkali activator C includes, but is not limited to, one or more of Na2CO3, KCO3, Na3PO4, KPO4, NaF and KF.
[0010] In any embodiment, the water reducing agent is a concrete water reducing agent with water reducing function.
[0011] In any embodiment, the solid alkali activator B includes one or both of NaOH and KOH.
[0012] Furthermore, the present invention also proposes a method for preparing the above-mentioned geopolymer concrete dry mix, comprising the following steps: mixing mineral powder, fly ash, and silica fume to obtain powder mixture N1; mixing solid alkali activator A, solid alkali activator B, solid alkali activator C, and water-reducing agent to obtain powder mixture N2; and mixing powder mixture N1, powder mixture N2, and quartz sand to obtain the geopolymer concrete dry mix.
[0013] In any embodiment, mixing for 5-10 minutes yields powder mixture N1; and / or mixing for 3-5 minutes yields powder mixture N2; and / or mixing for 10-15 minutes yields geopolymer concrete dry mix.
[0014] Furthermore, the present invention also proposes the application of the above-mentioned geopolymer concrete dry mix or the geopolymer concrete dry mix prepared by the above-mentioned preparation method in the preparation of concrete components.
[0015] In any embodiment, the above application includes the following steps: mixing geopolymer concrete dry mix with water to obtain a first mixture, then adding steel fibers and mixing to obtain a second mixture, pouring the second mixture into a mold, vibrating to compact it, and then curing it to obtain a concrete component.
[0016] In any embodiment, the dry-mixed geopolymer concrete is mixed with water at a mass ratio of 1:(0.14-0.2).
[0017] In any embodiment, the amount of steel fiber added is 2-3% of the volume of the first mixture.
[0018] In any embodiment, the steel fiber has a length of 6-30 mm and a diameter of 0.12-0.2 mm.
[0019] In any embodiment, the curing includes curing at room temperature followed by demolding, and then standard curing or steam curing.
[0020] Compared with existing technologies, the beneficial effects of this invention include: This invention proposes a single-component UHPGC dry mix design incorporating a ternary solid activator system. This system consists of a silicate activator, a caustic alkali activator, and a weak acid salt activator. These three components synergistically activate silica-alumina minerals, achieving the goal of promoting the formation of a high-density gel structure while controlling the solidification rate. Specifically, the solid weak acid salt activator preferentially reacts with Ca dissolved in the system during the initial stage of water addition. 2+ The polymer binds to form insoluble precipitates and builds a physical barrier on the particle surface, effectively delaying the polymerization reaction and giving the material excellent retarding properties. This overcomes the problems of short initial setting time and limited strength caused by traditional liquid weak acid salt activators that accelerate setting. Therefore, the geopolymer concrete dry mix proposed in this invention results in concrete components with long initial setting time and high strength.
[0021] Furthermore, this invention effectively enhances the crack resistance and toughness of the geopolymer matrix by introducing a steel fiber reinforcement mechanism, synergistically improving its brittle behavior. By constructing a synergistic mechanism between a ternary activator system and steel fibers, and employing an all-solid single-component design, this invention systematically solves the core problems of traditional geopolymers, such as insufficient strength, low toughness, and excessively fast setting rates. The ternary activator effectively regulates the setting process and promotes the formation of a dense cementitious structure; the introduction of steel fibers significantly improves the matrix toughness and interfacial bonding performance; and the all-solid formulation simplifies the construction process and improves the material's storage stability and on-site adaptability. This technology achieves synergistic optimization between mechanical and construction performance, providing strong support for the widespread application of ultra-high performance geopolymer concrete in complex engineering scenarios. Detailed Implementation
[0022] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it is understood that ranges of 60–110 and 80–120 are also expected. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "a–b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0023] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0024] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0025] This specific embodiment provides a dry-mixed geopolymer concrete. The raw materials, calculated by weight, include 20-85 parts mineral powder; 10-35 parts fly ash; 5-30 parts silica fume; 5-20 parts solid alkali activator A; 2-10 parts solid alkali activator B; 0.5-10 parts solid alkali activator C; 0-10 parts water-reducing agent; and 50-200 parts quartz sand. Solid alkali activator A is a silicate-type activator, Na₂O·nSiO₂ (n = 1-3.5); solid alkali activator B is a caustic alkali-type activator, comprising one or both of NaOH and KOH; solid alkali activator C is a weak acid-strong base salt, the solubility product of which is lower than that of hydrated calcium silicate, allowing it to form a low-solubility precipitate with calcium ions in the system, thereby delaying the formation of hydrated calcium silicate and achieving a retarding effect. Its anions react with dissolved Ca... 2+ It can react to form insoluble calcium salt precipitates, which delay coagulation through a physical barrier effect.
[0026] In some embodiments, the solid alkali activator C includes, but is not limited to, one or more of Na2CO3, KCO3, Na3PO4, KPO4, NaF, and KF. The total Na2O content of the solid alkali activators A, B, and C accounts for 3-8% of the total mass of the cementitious material (cementitious material includes mineral powder, fly ash, and silica fume), and the setting and hardening are synergistically optimized by controlling the liquid phase alkalinity and the silica-alumina dissolution rate. In some embodiments, the water-reducing agent is a concrete water-reducing agent with water-reducing function, preferably a polycarboxylate high-efficiency water-reducing agent dry powder, and the quartz sand particle size is less than 5 mm.
[0027] Furthermore, this specific embodiment also proposes a method for preparing the above-mentioned geopolymer concrete dry mix, including the following steps: mixing mineral powder, fly ash, and silica fume for 5-10 minutes to obtain powder mixture N1; mixing solid alkali activator A, solid alkali activator B, solid alkali activator C, and water-reducing agent for 3-5 minutes to obtain powder mixture N2; and mixing powder mixture N1, powder mixture N2, and quartz sand for 10-15 minutes to obtain the geopolymer concrete dry mix.
[0028] This specific embodiment also proposes the application of the above-mentioned geopolymer concrete dry mix or the geopolymer concrete dry mix prepared by the above-mentioned method in the preparation of concrete components, including the following steps: mixing the geopolymer concrete dry mix with water at a mass ratio of 1:(0.14-0.2) to obtain a first mixture, then adding steel fibers at a volume of 2-3% of the first mixture to obtain a second mixture, pouring the second mixture into a mold, vibrating to compact it, and then curing to obtain a concrete component; the steel fibers have a length of 6-30 mm and a diameter of 0.12-0.2 mm; the curing includes curing at room temperature, followed by demolding, and then standard curing or steam curing. Standard curing is curing at a temperature of 20±2℃ and a relative humidity of ≥95%; steam curing is curing at a temperature of 80±5℃ for 24 hours.
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0030] In this invention, the terms "some embodiments," "this embodiment," and examples are used to describe a subset of all possible embodiments. However, it is understood that "some embodiments" can be the same subset or different subsets of all possible embodiments and can be combined with each other without conflict.
[0031] If the application documents contain similar descriptions such as "first / second", the following explanation shall be added: In the following description, the terms "first / second / third" are used only to distinguish similar objects and do not represent a specific ordering of objects. It is understood that "first / second / third" may be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in a different order than that described herein.
[0032] In this embodiment, the term "and / or" merely describes the relationship between related objects, indicating that three relationships can exist. For example, object A and / or object B can represent: object A existing alone, object A and object B existing simultaneously, or object B existing alone. The water-reducing agent used in the following embodiments or comparative examples is polycarboxylate superplasticizer dry powder, and the quartz sand particle size is less than 5mm. The mineral powder is S95 grade slag powder with a specific surface area greater than 300m². 2 / kg; fly ash meets the relevant requirements of GB / T 1596 "Fly Ash for Cement and Concrete"; silica fume, specific surface area greater than 18000m² 2 / kg, SiO2 content greater than 90%. The solid alkali activator A is a silicate type activator, Na2O·nSiO2 (n=0.5-3.5); the solid alkali activator B is a caustic alkali type activator, NaOH; the solid alkali activator C is one or more of the following weak acid strong base salts: Na2CO3, KCO3, Na3PO4, KPO4, NaF, and KF.
[0033] Example 1
[0034] This embodiment proposes a dry-mixed geopolymer concrete. The raw materials, calculated by weight, include 74 parts mineral powder, 16 parts fly ash, 10 parts silica fume, 10 parts solid alkali activator A, 3.5 parts solid alkali activator B, 1 part solid alkali activator CNa2CO3, 2.5 parts water-reducing agent, and 100 parts quartz sand. The mineral powder is S95 grade slag powder with a specific surface area of 480 m². 2 / kg; the fly ash is Class F fly ash with a specific surface area of 420m². 2 / kg; silica fume, specific surface area 20000m² 2 / kg, with a SiO2 content of 95%.
[0035] This embodiment also proposes a method for preparing the above-mentioned geopolymer concrete dry mix, including the following steps:
[0036] Mineral powder, fly ash, and silica fume are mixed in a high-speed mixer for 8 minutes to obtain powder mixture N1; solid alkali activator A, solid alkali activator B, solid alkali activator C, and water-reducing agent are mixed in a high-speed mixer for 4 minutes to obtain powder mixture N2; powder mixture N1, powder mixture N2, and quartz sand are mixed in a high-speed mixer for 12 minutes to obtain the geopolymer concrete dry mix.
[0037] This embodiment also proposes the application of the above-mentioned geopolymer concrete dry mix in the preparation of concrete components, including the following steps:
[0038] The obtained dry mix was sealed and packaged. The dry mix of geopolymer concrete and water was mixed at a mass ratio of 1:0.15 to obtain a first mixture. Then, steel fibers were added at a volume of 2.5% of the first mixture to obtain a second mixture. The second mixture was poured into a mold, vibrated to compact, and then cured to obtain a concrete component. The steel fibers were 13 mm long and 0.2 mm in diameter, accounting for 1.5% of the volume of the first mixture, and straight steel fibers with a length of 6 mm and a diameter of 0.12 mm accounted for 1% of the volume of the first mixture. The mixture was stirred in a mixer for 6 minutes until it exhibited good fluidity and uniformity. The mixture was poured into a mold and vibrated to compact. After curing at room temperature for 24 hours, the mixture was demolded and then cured under standard conditions for 28 days to obtain a single-component ultra-high performance geopolymer concrete sample.
[0039] The obtained single-component ultra-high performance geopolymer concrete sample had a flowability of 210 mm, an initial setting time of 165 minutes, a final setting time of 255 minutes, a 28-day compressive strength of 150 MPa, a 28-day flexural strength of 18 MPa, a direct tensile strength of 5 MPa, and a peak tensile strain of 1500 με.
[0040] Example 2
[0041] This embodiment proposes a dry-mixed geopolymer concrete. The raw materials, calculated by weight, include 20 parts mineral powder, 35 parts fly ash, 5 parts silica fume, 20 parts solid alkali activator A, 2 parts solid alkali activator B, 10 parts solid alkali activator CNa2CO3, 0.5 parts water-reducing agent, and 200 parts quartz sand. The mineral powder is S95 grade slag powder with a specific surface area of 500 m². 2 / kg; the fly ash is Class F fly ash with a specific surface area of 450m². 2 / kg; silica fume, specific surface area 18000m² 2 / kg, with a SiO2 content of 92%.
[0042] This embodiment also proposes a method for preparing the above-mentioned geopolymer concrete dry mix, including the following steps:
[0043] Mineral powder, fly ash, and silica fume are mixed in a high-speed mixer for 9 minutes to obtain powder mixture N1; solid alkali activator A, solid alkali activator B, solid alkali activator C, and water-reducing agent are mixed in a high-speed mixer for 5 minutes to obtain powder mixture N2; powder mixture N1, powder mixture N2, and quartz sand are mixed in a high-speed mixer for 15 minutes to obtain the geopolymer concrete dry mix.
[0044] This embodiment also proposes the application of the above-mentioned geopolymer concrete dry mix in the preparation of concrete components, including the following steps:
[0045] The obtained dry mix was sealed and packaged. The dry mix of geopolymer concrete and water was mixed at a mass ratio of 1:0.14 to obtain the first mixture. Then, 2% by volume of mixed steel fibers was added to the first mixture and mixed for 7 minutes to obtain the second mixture, until the mixture exhibited good fluidity and homogeneity. The mixture was poured into a mold and compacted by vibration. After curing at room temperature for 24 hours, the mixture was demolded and then cured under standard conditions for 28 days to obtain a single-component ultra-high performance geopolymer concrete sample. Straight steel fibers with a length of 8 mm and a diameter of 0.12 mm accounted for 0.4% of the volume of the first mixture, and straight steel fibers with a length of 13 mm and a diameter of 0.12 mm accounted for 1.6% of the volume of the first mixture.
[0046] The obtained single-component ultra-high performance geopolymer concrete sample had a flowability of 215 mm, an initial setting time of 180 minutes, a final setting time of 260 minutes, a 28-day compressive strength of 160 MPa, a 28-day flexural strength of 21 MPa, a direct tensile strength of 6 MPa, and a peak tensile strain of 1600 με.
[0047] Example 3
[0048] This embodiment proposes a dry-mixed geopolymer concrete. The raw materials, calculated by weight, include 85 parts mineral powder, 10 parts fly ash, 30 parts silica fume, 5 parts solid alkali activator A, 10 parts solid alkali activator B, 0.5 parts solid alkali activator CNA3PO4, 10 parts water-reducing agent, and 50 parts quartz sand. The mineral powder is S95 grade slag powder with a specific surface area of 460 m². 2 / kg; the fly ash is Class F fly ash with a specific surface area of 430m². 2 / kg; silica fume, with a specific surface area of 22000m² 2 / kg, with a SiO2 content of 96%.
[0049] This embodiment also proposes a method for preparing the above-mentioned geopolymer concrete dry mix, including the following steps:
[0050] Mineral powder, fly ash, and silica fume are mixed in a high-speed mixer for 7 minutes to obtain powder mixture N1; solid alkali activator A, solid alkali activator B, solid alkali activator C, and water-reducing agent are mixed in a high-speed mixer for 3 minutes to obtain powder mixture N2; powder mixture N1, powder mixture N2, and quartz sand are mixed in a high-speed mixer for 10 minutes to obtain the geopolymer concrete dry mix.
[0051] This embodiment also proposes the application of the above-mentioned geopolymer concrete dry mix in the preparation of concrete components, including the following steps:
[0052] The obtained dry mix was sealed and packaged. The dry mix of geopolymer concrete and water was mixed at a mass ratio of 1:0.15 to obtain the first mixture. Then, steel fibers at a volume of 3% of the first mixture were added and mixed for 8 minutes to obtain the second mixture, until the mixture exhibited good fluidity and uniformity. The mixture was poured into a mold and compacted by vibration. After curing at room temperature for 24 hours, the mixture was demolded and then cured under standard conditions for 28 days to obtain a single-component ultra-high performance geopolymer concrete sample. Straight steel fibers with a length of 8 mm and a diameter of 0.12 mm accounted for 0.4% of the volume of the first mixture, and straight steel fibers with a length of 13 mm and a diameter of 0.12 mm accounted for 1.6% of the volume of the first mixture.
[0053] The obtained single-component ultra-high performance geopolymer concrete sample had a flowability of 215 mm, an initial setting time of 180 minutes, a final setting time of 250 minutes, a 28-day compressive strength of 160 MPa, a 28-day flexural strength of 22 MPa, a direct tensile strength of 7 MPa, and a peak tensile strain of 1700 με.
[0054] Example 4
[0055] This embodiment proposes a dry-mixed geopolymer concrete. The raw materials, calculated by weight, include 52 parts mineral powder, 22 parts fly ash, 17 parts silica fume, 12 parts solid alkali activator A, 6 parts solid alkali activator B, 5 parts solid alkali activator CNAF, 5 parts water-reducing agent, and 125 parts quartz sand. The mineral powder is S95 grade slag powder with a specific surface area of 520 m². 2 / kg; the fly ash is Class F fly ash with a specific surface area of 430m². 2 / kg; silica fume, specific surface area 19000m² 2 / kg, with a SiO2 content of 94%.
[0056] This embodiment also proposes a method for preparing the above-mentioned geopolymer concrete dry mix, including the following steps:
[0057] Mineral powder, fly ash, and silica fume are mixed in a high-speed mixer for 8 minutes to obtain powder mixture N1; solid alkali activator A, solid alkali activator B, solid alkali activator C, and water-reducing agent are mixed in a high-speed mixer for 4 minutes to obtain powder mixture N2; powder mixture N1, powder mixture N2, and quartz sand are mixed in a high-speed mixer for 13 minutes to obtain the geopolymer concrete dry mix.
[0058] This embodiment also proposes the application of the above-mentioned geopolymer concrete dry mix in the preparation of concrete components, including the following steps:
[0059] The obtained dry mix was sealed and packaged. The dry mix of geopolymer concrete and water was mixed at a mass ratio of 1:0.15 to obtain the first mixture. Then, steel fibers at a volume of 3% of the first mixture were added and mixed for 6 minutes to obtain the second mixture, until the mixture exhibited good fluidity and uniformity. The mixture was poured into a mold and compacted by vibration. After curing at room temperature for 24 hours, the mixture was demolded and then cured under standard conditions for 28 days to obtain a single-component ultra-high performance geopolymer concrete sample. Straight steel fibers with a length of 30 mm and a diameter of 0.2 mm accounted for 2% of the volume of the first mixture, and straight steel fibers with a length of 6 mm and a diameter of 0.12 mm accounted for 1% of the volume of the first mixture.
[0060] The obtained single-component ultra-high performance geopolymer concrete sample had a flowability of 210 mm, an initial setting time of 160 minutes, a final setting time of 225 minutes, a 28-day compressive strength of 150 MPa, a 28-day flexural strength of 22 MPa, a direct tensile strength of 6 MPa, and a peak tensile strain of 1500 με.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 1 is that the amount of solid alkali activator B is 4.3 parts and the amount of solid alkali activator CNa2CO3 is 0.2 parts, while the other components and amounts are the same as in Example 1.
[0063] The preparation method of the geopolymer concrete dry mix in this comparative example is the same as that in Example 1.
[0064] The specific steps for applying the dry-mixed geopolymer concrete of this comparative example in the preparation of concrete components are the same as those in Example 1. The obtained single-component ultra-high performance geopolymer concrete sample has a flowability of 180 mm, an initial setting time of 60 minutes, a final setting time of 130 minutes, a 28-day compressive strength of 118 MPa, a 28-day flexural strength of 13.5 MPa, a direct tensile strength of 3.2 MPa, and a peak tensile strain of 850 με.
[0065] Comparative Example 2
[0066] The difference between this comparative example and Example 1 is that 8 parts of solid alkali activator C Na2CO3 were used, while the other components and amounts were the same as in Example 1.
[0067] The preparation method of the geopolymer concrete dry mix in this comparative example is the same as that in Example 1.
[0068] The specific steps for applying the dry-mixed geopolymer concrete of this comparative example in the preparation of concrete components are the same as those in Example 1. The 28-day compressive strength of the obtained single-component ultra-high performance geopolymer concrete sample is 96 MPa, the fluidity is 220 mm, the initial setting time is 200 minutes, the final setting time is 310 minutes, the 28-day compressive strength is 130 MPa, the 28-day flexural strength is 15 MPa, the direct tensile strength is 4 MPa, and the peak tensile strain is 1400 με.
[0069] Other beneficial effects:
[0070] Compared with the prior art, the present invention has the following advantages:
[0071] 1) Cementitious Material System Design: The proportions of mineral powder, fly ash, and silica fume were optimized to create a complementary and synergistic effect. Mineral powder provides abundant Ca, Si, and Al elements, serving as the main reaction source for CASH gel; fly ash is rich in active aluminum, participating in the formation of NASH gel; silica fume not only acts as a highly active silicon source to enhance the degree of polymerization but also refines the pore structure and improves the material's density through physical filling. The organic combination of these three materials significantly enhances the compactness of the cementitious structure and the overall mechanical properties of the system.
[0072] 2) Ternary activator system design: Silicate-type activators, caustic alkali-type activators, and weak acid salt-type activators are mixed in a specific ratio to form a synergistic activation system. The silicate activator provides OH- and soluble silicon sources, promoting CASH and NASH gel formation; the caustic alkali-type activator acts as an auxiliary activator, rapidly releasing high concentrations of OH-. - It significantly increases the initial alkalinity and accelerates the initiation process of the activation reaction; the weak acid salt activator plays a role in retarding and regulating coagulation, and can react with the dissolved Ca in the early stage. 2+ Al 3+ The reaction produces insoluble phosphate precipitates, forming a physical barrier layer that effectively slows down the nucleation rate and gel polymerization process, precisely controlling the slurry setting time and significantly improving construction adaptability. The synergistic effect of these three factors ensures a retarding effect while significantly improving material strength, breaking through the performance bottleneck of traditional systems characterized by "rapid setting and low strength."
[0073] 3) Condensation and hardening regulation mechanism: The ternary activator system achieves precise control of condensation behavior by adjusting alkalinity, ion solubility, and crystal nucleation rate. The precipitation barrier formed early by the solid phosphate activator delays the induction period of the hydration reaction, preventing excessively rapid condensation; subsequently, Ca... 2+ -OH- binding promotes rapid gelation of CASH, ensuring early strength; continuous dissolution of fly ash provides an aluminum-silicon source, constructing a dense NASH gel network, thereby improving long-term mechanical properties and durability.
[0074] 4) Physicochemical effects of silica fume: Silica fume dissolves rapidly in the early stages of the reaction, consuming OH- ions, regulating the pH value and degree of silicate polymerization, controlling the dissolution rate of the cementitious material, and indirectly inhibiting the excessively rapid activation reaction. In addition, the highly active Si released by silica fume can participate in the formation of various gel structures, and the unreacted fine particles effectively fill the pores, further improving the density and durability of the material.
[0075] 5) Steel fiber reinforcement and toughening mechanism: Introducing steel fibers with specific aspect ratios, especially high aspect ratio straight steel fibers, can effectively bridge cracks, prevent crack propagation, and significantly improve the toughness and crack resistance of the matrix. By mixing steel fibers of various lengths, a multi-scale toughening system is formed, which not only improves compressive strength but also significantly enhances flexural tensile properties, thereby improving the overall structural performance and deformation coordination of the material.
[0076] 6) Advantages of Single-Component Dry Mix: This invention adopts an all-solid, single-component dry mix design. All components are pre-mixed in the factory, ensuring uniform mixing and precise metering, avoiding errors and quality fluctuations caused by on-site multi-component feeding. The dry mix only requires the addition of water and steel fibers for mixing on-site, greatly simplifying the construction process and improving efficiency and safety. The solid activator replaces the liquid activator, eliminating storage and transportation inconveniences and safety risks, facilitating large-scale, standardized application.
[0077] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A dry-mixed geopolymer concrete, characterized in that, The raw materials, calculated by weight, include 20-85 parts mineral powder; 10-35 parts fly ash; 5-30 parts silica fume; 5-20 parts solid alkali activator A; 2-10 parts solid alkali activator B; 0.5-10 parts solid alkali activator C; 0-10 parts water-reducing agent; and 50-200 parts quartz sand. Solid alkali activator A is a silicate-type activator; solid alkali activator B is a caustic alkali-type activator; and solid alkali activator C is a weak acid-strong base salt.
2. The geopolymer concrete dry mix according to claim 1, characterized in that, The solid alkali activator C includes, but is not limited to, one or more of Na2CO3, KCO3, Na3PO4, KPO4, NaF, and KF.
3. The dry concrete mix according to claim 1, characterized in that, The water-reducing agent is a concrete water-reducing agent with water-reducing function.
4. The geopolymer concrete dry mix according to claim 1, characterized in that, The solid alkali activator B includes one or both of NaOH and KOH.
5. A method for preparing a geopolymer concrete dry mix according to any one of claims 1-4, characterized in that, The process includes the following steps: mixing mineral powder, fly ash, and silica fume to obtain powder mixture N1; mixing solid alkali activator A, solid alkali activator B, solid alkali activator C, and water-reducing agent to obtain powder mixture N2; and mixing powder mixture N1, powder mixture N2, and quartz sand to obtain the geopolymer concrete dry mix.
6. The method for preparing geopolymer concrete dry mix according to claim 5, characterized in that, Mix for 5-10 minutes to obtain powder mixture N1; and / or, mix for 3-5 minutes to obtain powder mixture N2; and / or, mix for 10-15 minutes to obtain geopolymer concrete dry mix.
7. The application of a geopolymer concrete dry mix according to any one of claims 1-4 or a geopolymer concrete dry mix prepared by the preparation method according to any one of claims 5-6 in the preparation of concrete components.
8. The application according to claim 7, characterized in that, The process includes the following steps: mixing geopolymer dry mix with water to obtain a first mixture, then adding steel fibers and mixing to obtain a second mixture, pouring the second mixture into a mold, vibrating to compact it, and then curing it to obtain a concrete component.
9. The application according to claim 7, characterized in that, The geopolymer concrete dry mix and the water are mixed at a mass ratio of 1:(0.14-0.2).
10. The application according to claim 7, characterized in that, The amount of steel fiber added is 0.5-4% of the volume of the first mixture; the steel fiber has a length of 6-30 mm and a diameter of 0.12-0.2 mm.
Citation Information
Patent Citations
Solid waste cementing material as well as preparation and application methods thereof
CN119330616A
Cited By
Solid alkali-activated geopolymer cement mortar rapid repair cement pavement material and preparation method thereof
CN118063156A